2019
DOI: 10.1093/ofid/ofz275
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Invasive Group A Streptococcal Disease and Emergence of Mucoid Strains in a Pediatric Population: February–June 2017

Abstract: Background Infection with group A Streptococcus (GAS) can cause severe systemic and locally invasive disease. Invasive group A streptococcal (iGAS) disease incidence varies both seasonally and year-to-year, and it may exhibit clustered outbreaks. We observed an upswing in iGAS cases at a tertiary care Children’s Hospital, prompting further characterization of local iGAS disease. Methods Cases of iGAS disease were abstracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
0
1
Order By: Relevance
“…In group I (0-18 age group) Staphylococcus aureus has the highest incidence in the summer, the lowest in the autumn (p = 0.0192). In agreement with the literature [1,2,6,23,38,39], we consider the findings regarding the seasonality of the individual microbial agents interesting from an epidemiological point of view. From a clinical point of view, the treatment strategy remains the same.…”
Section: The Spectrum Of Microbial Agents Based On Gender Age and Sesupporting
confidence: 91%
See 1 more Smart Citation
“…In group I (0-18 age group) Staphylococcus aureus has the highest incidence in the summer, the lowest in the autumn (p = 0.0192). In agreement with the literature [1,2,6,23,38,39], we consider the findings regarding the seasonality of the individual microbial agents interesting from an epidemiological point of view. From a clinical point of view, the treatment strategy remains the same.…”
Section: The Spectrum Of Microbial Agents Based On Gender Age and Sesupporting
confidence: 91%
“…Differences in the PTA incidence in individual periods of the year (spring, summer, autumn, and winter) are not significant in our group (p = 0.4396), nor were they significant in studies from Denmark, England, or the USA [13,23,37]. Other studies have reported significant differences in the seasonal incidence of PTA in a group of pediatric patients with the highest incidence in the spring or summer [6,38,39]. In our work, a detailed analysis revealed that the incidence of PTA in boys in group I (0-18 years) is statistically significantly higher during the summer and, conversely, is at its lowest in the autumn (p = 0.0023).…”
Section: The Spectrum Of Microbial Agents Based On Gender Age and Secontrasting
confidence: 70%